Partial discharge pattern analysis using statistical technique in XLPE cable under various soil conditions - Mansor M.; Ghani A.B.A.; Ghosh P.S. (2023)
Partial discharge (PD) detection and monitoring has gained a paramount interest to all engineers involved in the design of high voltage insulation. Although, the phenomenon of partial discharges in power cables are well known but the effect of soil thermodynamics on PD is not yet well established. An experiment has been carried out to assess the effect of soil thermal resistivity on various PD parameters. The cable sample studied is an 11 kV, single core, 240-mm2 XLPE cable. PD patterns are obtained in the form of 2-dimentional statistical distribution. In PD pattern analysis, the most vital stage is "classification". Classification aims at the recognition of patterns from different origin e.g. soil conditions in this present research. In this paper, the classification of PD patterns has been carried out using "Statistical Technique". To identify the characteristic shape of the PD patterns, 30 well known classifiers are used. Once the values of the classifier parameters are known for a given soil condition, then they serve as standard values. These standard values are then used to recognise and classify the PD patterns recorded from other soil conditions.